Vitamin D Enhanced the Osteogenic Differentiation of Cell Spheroids Composed of Bone Marrow Stem Cells - Hyun-Jin Lee; Young-Min Song; Seunghoon Baek; Yoon-Hee Park; Jun-Beom Park (Medicina, 2021)
Background and Objectives: Vitamin D is a bone modulator widely used in regenerative medicine. This study aimed to analyze the effects of vitamin D on the osteogenic differentiation and mineralization of human mesenchymal stem cells. Materials and Methods: Spheroids were fabricated using human bone marrow-derived stem cells, and were cultured in the presence of vitamin D at concentrations of 0, 0.1, 1, 10, and 100 nM. Stem cell spheroids were fabricated and the morphological evaluation was conducted on days 1, 3, 7 and 14. Determination of qualitative cellular viability was performed with Live/Dead Kit assay on days 1 and 7. Quantitative cellular viability was evaluated with Cell Counting Kit-8 on days 1, 3, 7, and 14. To analyze the osteogenic differentiation of cell spheroids, alkaline phosphatase activity assays were performed with commercially available kit on days 7 and 14. Real-time polymerase chain reaction was used to determine the expression levels of RUNX2, BSP, OCN, and COL1A1 on days 7 and 14. Results: The stem cells produced well-formed spheroids, and addition of vitamin D did not result in any noticeable changes in the shape. The addition of vitamin D did not significantly change the diameter of the spheroids at 0, 0.1, 1, 10, or 100 nM concentrations. Quantitative cell viability results from days 1, 3, 7 and 14 showed no significant difference between groups (p > 0.05). There was significantly higher alkaline phosphatase activity in the 0.1 nM group when compared with the control group on day 14 (p < 0.05). Real-time polymerase chain reaction results demonstrated that the mRNA expression levels of RUNX2, OCN, and COL1A1 were significantly increased when vitamin D was added to the culture. Conclusions: Based on these findings, we concluded that vitamin D could be applied to the increased osteogenicity of stem cell spheroids.